Legal Certainty in the Execution of Death Sentences after Indonesia's 2023 Criminal Code: Probationary Death Sentence, Lex Favor Reo, and Transitional Governance - Putu Oka Bhismaning; Diah Ratna Sari Hariyanto (International Journal of Business, Law, and Education, 2026)
This article examines the legal certainty of death-sentenced prisoners in Indonesia after the enactment and entry into force of Law Number 1 of 2023 concerning the Criminal Code. The new Code does not abolish capital punishment, but relocates it outside the category of principal punishments and defines it as a special, alternative, and last-resort sanction. The most significant innovation is the ten-year probationary death sentence under Article 100, which allows commutation into life imprisonment when the prisoner demonstrates commendable conduct and a realistic prospect of rehabilitation. Using normative legal research, this article applies statutory, conceptual, case-based, and comparative human rights approaches to analyse Articles 3, 67, 98-102, 618, and related provisions of the National Criminal Code, the Clemency Law, the new Criminal Procedure Code, selected judicial decisions, policy reports, and international human rights materials. The article argues that Article 100 is structurally attached to the sentencing stage because the probationary period must be expressly stated in the judgment. Consequently, it cannot automatically govern prisoners whose death sentences became final before the new Code took effect, unless an implementing or transitional statute creates a specific conversion mechanism. The article contributes to the literature by distinguishing three legal pathways: prospective probation under Article 100, post-clemency conversion after ten years of non-execution under Article 101, and limited retroactive adjustment under Article 3(7) based on lex favor reo. It concludes that legal certainty requires an implementing statute under Article 102 that establishes objective assessment criteria, competent institutional authority, procedural safeguards, reasoned decisions, and a transitional regime for existing death row prisoners.